2019
DOI: 10.1093/ofid/ofz360.2177
|View full text |Cite
|
Sign up to set email alerts
|

2499. Perceptions of and Preferences for Oral or Long-Acting Injectable Antiretroviral Treatment Regimens in the United States and Canada

Abstract: BackgroundAntiretroviral treatment (ART) for patients living with HIV (PLHIV) has improved greatly, however, challenges with daily oral dosing remain. New ART options with reduced dosing frequency and innovative delivery methods may help address these challenges. This study assesses patient and physician satisfaction with current treatments and preferences for switching to a monthly or every other month long-acting injectable (LAI) ART.MethodsThis is a cross-sectional online survey of PLHIV and physicians trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As previously discussed, potential benefits anticipated with the first complete parenteral regimen for HIV included increased convenience, reduced inadvertent HIV status disclosure, and removal of the daily reminder to the patient of their HIV status. These predictions held largely true with improved confidentiality and flexibility being reported by patients participating in several of the clinical trials for CAB/RPV 29–34 …”
Section: Efficacymentioning
confidence: 82%
“…As previously discussed, potential benefits anticipated with the first complete parenteral regimen for HIV included increased convenience, reduced inadvertent HIV status disclosure, and removal of the daily reminder to the patient of their HIV status. These predictions held largely true with improved confidentiality and flexibility being reported by patients participating in several of the clinical trials for CAB/RPV 29–34 …”
Section: Efficacymentioning
confidence: 82%
“…They additionally reported that such an injection may reduce chances that others would discover their diagnosis. 21 Further study is needed on these social and environmental factors, which may prove advantageous when attempting to engage patients in challenging or highly-stigmatized locations and settings.…”
Section: Resultsmentioning
confidence: 99%
“…While minimal data do exist in this area, none represent the full landscape of upcoming treatment options under development. [19][20][21][22] Our study seeks to further describe patient acceptability of long-acting injectable antiretrovirals through the presentation of multiple formulation and delivery factors.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the possibility of a transitional oral treatment was also explored, in case the patient could not receive the intramuscular dosage, and the result has been satisfactory [ 130 ]. In addition, the stigma experienced by people living with HIV may be alleviated by the possibility of switching from oral to injectable treatment, particularly when administered as a long-acting treatment such as CARLA [ 131 ].…”
Section: Parenteral Antiretroviral Therapy: How Often? Could It Be An...mentioning
confidence: 99%